MODIFIKASI CEROBONG WET SCRUBBER UNTUK MENURUNKAN KADAR DEBU DAN KEPEKATAN ASAP PADA SUMBER EMISI TIDAK BERGERAK - Siti Nuryani; Sigid Sudaryanto; Sardjito Eko Windarso; Joko Malis Sunarno (Jurnal Ilmiah Medsains, 2021)
The air quality in the environment is decreasing. Human activity is the main factor causing the decline in air quality in the environment. Changes in the air environment are caused by air pollution, namely the entry of pollutants (in the form of gases and small particles / aerosols) into the air. Pollutants that enter the air can be natural (smoke from forest fires, caused by volcanoes, meteorite dust, and salt emission from the sea) and human activities (transportation, industrial waste disposal). The concentration of air pollution in several big cities and industrial areas of Indonesia causes respiratory problems, irritation of the eyes and ears, the emergence of certain diseases and impaired visibility. Particles with a size between 0.01 – 5 m are the main source of air pollutants because their condition is not visible and continues to exist in the atmosphere for quite a long time. The purpose of the study was to determine the effect of chimney modifications on dust levels and smoke density as air pollution materials. Techniques for controlling particle emission are all based on capturing particles before they are released into the atmosphere. The method used to achieve this goal is influenced by the particle size. Some of the tools used for this purpose include gravity settling chamber systems, cyclone collectors, wet brush scrubbers and electrostatic precipitators. Environmental control is very necessary for the creation of a clean and healthy environment, it can be done by improving the quality of the tool and making modifications to node I, namely the pollutant source. an average of 0.2726 mg/L (54.2978%), and the parameter range of smoke density remains at levels 0 – 20%. The conclusion of the study is that there is a difference in the average dust content using a modified Wet Scrubber chimney but the smoke density parameter remains.